Organization climate, job stress and intention to leave among lecturers' in private higher learning institution in Sarawak - Nurashikin, Nazer Mohamed (Universiti Malaysia Sarawak (UNIMAS), 2013)
The general objective of this study was to investigate the relationship between organization climate, job stress and intention to leave among lecturers' in private higher learning institutions in Sarawak. A total of 200 questionnaires were distributed to the respondents of selected private higher learning institutions in Sarawak and 82.5% of it, which is 165 sets were returned.